2006
DOI: 10.1159/000091062
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Erosion and Abrasion by a High Fluoride Concentration Gel Applied at High Frequencies

Abstract: The aim of this study was to determine maximum attainable protection of enamel from erosion and erosion abrasion using a highly fluoridated gel with and without additional fluoride from toothpaste. Thirty-six bovine enamel specimens were subjected to six erosive attacks per day (1% citric acid with pH 2.3 for 30 s), while the rest of the day the specimens were in artificial saliva. There were four treatment groups (9 specimens in each group): fluoride-free toothpaste/saliva slurry twice daily (group T0), fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
68
1
26

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 41 publications
(20 reference statements)
8
68
1
26
Order By: Relevance
“…The efficacy of different fluoride compounds to decrease the progression of the erosive process has been demonstrated in several studies. 9,13 Thereby, most studies focused on fluoride compounds that have been used over years for caries prevention, such as sodium fluoride (NaF), stannous fluoride (SnF 2 ) or amine fluoride (AmF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of different fluoride compounds to decrease the progression of the erosive process has been demonstrated in several studies. 9,13 Thereby, most studies focused on fluoride compounds that have been used over years for caries prevention, such as sodium fluoride (NaF), stannous fluoride (SnF 2 ) or amine fluoride (AmF).…”
Section: Introductionmentioning
confidence: 99%
“…17 As high concentrated fluoride agents or a prolonged application time might lead to a thicker and more stable CaF 2 -precipitate, an intensive fluoridation is considered as most effective for prevention of erosive enamel loss. 4,13 While most studies focused on the impact of the fluoride concentration and the pH-value of the fluoride agent on erosion, only few studies compared the efficacy of fluorides with respect to the fluoride compound. Thereby, SnF 2 containing toothpastes and solutions showed a better protective capability against erosion-like lesions than NaF agents.…”
Section: Introductionmentioning
confidence: 99%
“…15 Generally, the fluoridation of bleached enamel is frequently recommended for improving microhardness 7,14 and, thus, increasing the abrasion resistance of softened enamel. [16][17] However, there is no general agreement on the optimal time point of fluoridation during the bleaching regime. On one hand, the application of fluoride gels for several days prior to the bleaching treatment might be advisable, as fluoride increases the demineralization resistance of enamel and, therefore, might prevent microhardness loss during the subsequent bleaching treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, research into dental erosion focused on the antierosive potential of titanium tetrafluoride (TiF 4 ), which is suggested to be more effective in inhibition of enamel erosion or carious demineralisation than sodium, stannous or amine fluoride. [4][5][6][7] Hove et al 5 reported that TiF 4 (0.5 M F) reduced enamel erosion almost completely (88%), while SnF 2 and NaF treatment resulted in only 50% or 25% protection, respectively.…”
Section: Introductionmentioning
confidence: 99%